Assessing regional left ventricular thickening dysfunction and dyssynchrony via personalized modeling and 3D wall thickness measurements for acute myocardial infarction - Khalid, Amirah; Lim, Einly; Chan, Bee Ting; Abdul Aziz, Yang Faridah; Chee, Kok Han; Yap, Hwa Jen; Liew, Yih Miin (Wiley, 2019)
Background: Existing clinical diagnostic and assessment methods could be improved to facilitate early detection and treatment of cardiac dysfunction associated with acute myocardial infarction (AMI) to reduce morbidity and mortality. Purpose: To develop 3D personalized left ventricular (LV) models and thickening assessment framework for assessing regional wall thickening dysfunction and dyssynchrony in AMI patients. Study Type: Retrospective study, diagnostic accuracy. Subjects: Forty-four subjects consisting of 15 healthy subjects and 29 AMI patients. Field Strength/Sequence: 1.5T/steady-state free precession cine MRI scans; LGE MRI scans. Assessment: Quantitative thickening measurements across all cardiac phases were correlated and validated against clinical evaluation of infarct transmurality by an experienced cardiac radiologist based on the American Heart Association (AHA) 17-segment model. Statistical Test: Nonparametric 2-k related sample-based Kruskal–Wallis test; Mann–Whitney U-test; Pearson's correlation coefficient. Results: Healthy LV wall segments undergo significant wall thickening (P < 0.05) during ejection and have on average a thicker wall (8.73 ± 1.01 mm) compared with infarcted wall segments (2.86 ± 1.11 mm). Myocardium with thick infarct (ie, >50% transmurality) underwent remarkable wall thinning during contraction (thickening index [TI] = 1.46 ± 0.26 mm) as opposed to healthy myocardium (TI = 4.01 ± 1.04 mm). For AMI patients, LV that showed signs of thinning were found to be associated with a significantly higher percentage of dyssynchrony as compared with healthy subjects (dyssynchrony index [DI] = 15.0 ± 5.0% vs. 7.5 ± 2.0%, P < 0.01). Also, a strong correlation was found between our TI and left ventricular ejection fraction (LVEF) (r = 0.892, P < 0.01), and moderate correlation between DI and LVEF (r = 0.494, P < 0.01). Data Conclusion: The extracted regional wall thickening and DIs are shown to be strongly correlated with infarct severity, therefore suggestive of possible practical clinical utility. Level of Evidence: 2. Technical Efficacy: Stage 1. J. Magn. Reson. Imaging 2019;49:1006–1019. © 2018 International Society for Magnetic Resonance in Medicine